Eggs, emperors and empire: Apsley Cherry-Garrard’s ‘Worst journey’ as imperial quest Romance - Leane, Elizabeth (Research Online, 2014)
Antarctic exploration in the ‘Heroic Era’ (the early twentieth century) is often represented as the last gasp of British imperialism — an attempt to occupy empty, uninhabited and more-or-less useless territory at a time when the rest of the empire was beginning to crumble.1 Of British Heroic-Era exploits, three stories in particular preoccupy the present popular imagination2: Robert F. Scott’s ill-fated journey to the Pole with his four companions, as famously related in his posthumously published journal; a slightly earlier journey to Cape Crozier by three of Scott’s expedition members in search of Emperor penguins’ eggs, as told by Apsley Cherry-Garrard in a chapter of his 1922 travel memoir The Worst Journey in the World; and the story of Ernest Shackleton’s Imperial Trans- Antarctic Expedition, in which his ship, The Endurance, was imprisoned and later crushed by ice, leaving the men to survive on ice-floes and a subantarctic island.